A case of pediatric leukemia with multi drug resistant bacterial infections - Murugesan, Saravanan; Rudrapathy, Parthiban; Samuel, Sajani (International Journal of Contemporary Pediatrics, 2018)
Infections still remain a major cause of therapy-associated morbidity and mortality in pediatric cases with acute myeloid leukemia (AML). Down syndrome (DS) children have an approximately 10-20 fold higher incidence of acute leukemia and approximately 150 fold increased risk of developing myeloid leukemia of DS (ML-DS). Multi-drug resistant (MDR-GNB) Gram-negative bacterial septicaemia is an emerging global challenge. Authors are reporting a 4 and half year old boy with diagnosis Acute Megakaryocytic Leukemia (AMKL) who developed septicaemia and diaper rash. MDR E. coli was isolated and he was treated with fosfomycin followed by colistin. The boy developed cardiac arrest with chest compression and expired.